2015
DOI: 10.1108/ijbm-07-2014-0100
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the factors influencing the adoption of m-banking: a cross cultural study

Abstract: Purpose – Little is known about the adoption of mobile banking technologies in emerging Asian economies. The purpose of this paper is to empirically examine the motivators that influence a consumer’s intentions to use mobile banking. Design/methodology/approach – A web-based survey was employed to collect data from 348 respondents, split across Thailand and Australia. Data were analysed by employing exploratory and confirmatory factor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
104
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 114 publications
11
104
0
5
Order By: Relevance
“…Perceived usefulness is a key influence on consumer adoption of various self-service technologies (Kaushik & Raham, 2015;Mortimer et al, 2015;Yadav et al, 2015). Mobile payment interest is negatively influenced by UK consumer perceptions of technology and security risks including the lack of PIN authentication although the benefits and advantages can outweigh the risks for UK consumer in some very specific scenarios e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived usefulness is a key influence on consumer adoption of various self-service technologies (Kaushik & Raham, 2015;Mortimer et al, 2015;Yadav et al, 2015). Mobile payment interest is negatively influenced by UK consumer perceptions of technology and security risks including the lack of PIN authentication although the benefits and advantages can outweigh the risks for UK consumer in some very specific scenarios e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived usefulness is a key factor in mobile banking adoption (Mohammadi, 2015;Mortimer et al, 2015;Koenig-Lewis et al, 2010) whilst initial trust has a positive and direct effect on perceived usefulness with mobile banking (Zhou, 2011). Furthermore, the provision of a payment guarantee significantly increases consumer trust in the organisation which positively affects perceived usefulness (McKnight et al, 2002) but also reduces perceived risk (Gu et al, 2009) whilst trust and credibility are crucial in reducing perceived risk (Koenig-Lewis et al, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In a cross cultural study done by Mortimer et al(2015), it was found that in case of the adoption intention of Australian consumers, most important variables are, PU, PEOU and perceived risk (PR) and in case of Thailand, the variables are PU, PR and social influence.…”
Section: E) Integrating Trust and Tam In Case Of Mobile Bankingmentioning
confidence: 99%
“…Many studies were undertaken using TAM to understand the adoption of Mobile Banking across globe. (Kumar et al, 2017;Mortimer et al, 2015;Jeong & Yoon, 2013;Norzaidi et al, 2011;Luarn & Lin, 2005). This research took revised TAM framework (Davis, 1989) which was further undertaken many empirical studies which emphasized that PEoU and PU mediated effect of exterior factors on behavioral intention of users to adopt and use technology ( Davis, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%